Understanding the impact of crop and food production on the water environment ‐using sugar as a model - Hess, Tim M.; Aldaya, Maite; Fawell, John; Franceschini, Helen; Ober, Eric; Schaub, Ruediger; Schulze-Aurich, Jochen (Wiley, 2013)
The availability of fresh water and the quality of aquatic ecosystems are important global concerns, and agriculture plays a major role. Consumers and manufacturers are increasingly sensitive to sustainability issues related to processed food products and drinks. The present study examines the production of sugar from the growing cycle through to processing to the factory gate, and identifies the potential impacts on water scarcity and quality and the ways in which the impact of water use can be minimised. We have reviewed the production phases and processing steps, and how calculations of water use can be complicated, or in some cases how assessments can be relatively straightforward. Finally, we outline several ways that growers and sugar processors are improving the efficiency of water use and reducing environmental impact, and where further advances can be made. This provides a template for the assessment of other crops.
Keywords: Footprint; Impact; Sugar; Waste